Projection in snowfall characteristics over the European Alps and its sensitivity to the SST changes: results from a 50 km resolution AGCM. (19th May 2017) - Freychet, N.; Hsu, H.‐H.; Duchez, A.; Tu, C.‐Y.
Abstract: The end‐of‐century projection of the snowfall characteristics over the Alps region is studied using the 50‐km resolution atmospheric global climate model, HiRAM (high‐resolution atmospheric model). The model is forced by three different patterns of projections in the sea surface temperature (SST) in order to assess the sensitivity of snowfall characteristics to theses patterns. It is found that the mean snowfall intensity and frequency is poorly affected by the differences in SST forcing. However, the projections of heavy snowfall events strongly depend on the SST scenario. The changes in temperature and frequency of precipitation and freezing days over the Alps were investigated. We found that these variables did not exhibit a clear dependence to the SST scenario and could not explain the differences observed in snowfall projections. Changes in the moisture transport from the Atlantic Ocean to Europe were found significantly different between each scenario and are assumed to be the main factor affecting the projections of snowfalls, by providing more or less moisture supply. Abstract : The sensitivity of climate projections of snowfall events over the Alps to the patterns of sea surface temperature (SST) forcing are investigated with a global high‐resolution atmospheric model, forced by three SST scenario. It is found that the mean snowfall events are poorly affected by the SST scenario, while the heavy snowfall events have a higher sensitivity. The moisture transport from the Atlantic Ocean seems to be the main factor affecting the projections.